2004
DOI: 10.1097/01.sla.0000145927.29265.8a
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Primary Hyperparathyroidism

Abstract: The method of sampling PTH intraoperatively at 5 minutes has a high positive predictive value (99.5%) but a low negative predictive value (19.5%), which can lead to unnecessary explorations and a delay in the operative procedure. The negative predictive value increases substantially at 30 minutes and is best on the day after surgery. We suggest giving up the intraoperative measurement of PTH to adopt the first day postoperative measurement of PTH as a predictor of successful parathyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Additionally, in 38.5% of the cases who were converted to bilateral exploration in their study, conversion was unnecessary, since no additional pathologic gland was found. Similar findings with concordant imaging were described by several other groups [14][15][16][17]. These findings are currently reflected in the ESES guidelines stating that ioPTH is recommended mainly in cases of discordant or Fig.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Additionally, in 38.5% of the cases who were converted to bilateral exploration in their study, conversion was unnecessary, since no additional pathologic gland was found. Similar findings with concordant imaging were described by several other groups [14][15][16][17]. These findings are currently reflected in the ESES guidelines stating that ioPTH is recommended mainly in cases of discordant or Fig.…”
Section: Discussionsupporting
confidence: 86%
“…However, given the substantial advances in imaging techniques over the years which allow better indication to parathyroid localization, the added value of ioPTH has become questionable. Not surprisingly, a few publications have already demonstrated comparable cure rates of MIP without ioPTH monitoring [13][14][15][16][17]. Indeed, alongside to its advantages, there are some downsides to using ioPTH and these should all be calculated and discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Failure of PTH levels to fall significantly after excision of a single abnormal parathyroid gland leading to bilateral conversion has been also been reported in a number of other studies. [22][23][24] A study of 119 patients collected PTH results without disclosing these at the time of surgery.…”
mentioning
confidence: 99%